Platelets and Platelet Interaction with Progenitor Cells in Vascular Homeostasis and Inflammation - Sopova, Kateryna; Tatsidou, Prokopia; Stellos, Konstantinos (Current Vascular Pharmacology, 2012)
Platelet adhesion on vascular wall is the first step following vascular injury. Differential platelet secretion supports angiogenesis and vascular homeostasis. Progenitor cells are pluripotent cells responsible for tissue regeneration and wound healing. Upon ischemia bone marrow-derived progenitor cells are mobilized into peripheral circulation and domiciliate into peripheral organ vasculature and either give birth to a series of cardiovascular cells, including endothelial cells, macrophages, smooth muscle cells, or support in a paracrinic way the angiogenic capacity of local tissue cells. Mobilization, chemotaxis, adhesion, differentiation and interaction with vascular cells are essential steps of progenitor cellmediated tissue repair. This review summarizes the recent advances in our understanding of platelet function with focus on interaction with progenitor cells and its role in cardiovascular homeostasis. Moreover, the role of platelet microparticles in progenitor cell function is separately addressed. Understanding the mechanisms of platelet interaction with progenitor cells provides us with new insights in the mechanisms of vascular homeostasis and possible new therapeutical targets supporting vascular repair.
Keywords: angiogenesis